PENGARUH STRUKTUR DAN KOMPOSISI MANGROVE BAGI KERAPATAN NYAMUK DI DESA KOPI DAN DESA MINANGA KECAMATAN BINTAUNA. - Daniel F Masela (Universitas Sam Ratulangi, 2012)
ABSTRACDamage of Forest mangrove can cause at make-up of mosquito population as vectordisease. This research aim to learn the influence of structure and composition mangrove formosquito closeness in Countryside Kopi and Minanga. This Research is executed in forest ofmangrove Countryside Kopi and Countryside Minanga. Method analyse the vegetasimangrove use the random plot. Mosquito perception conducted at 7 located perception dotbetween forest of mangrove and settlement. Analyse the structure and composition mangroveuse the INP. Tabulation Mosquito Data pursuant to index dominansi. Difference of mosquitoCloseness two community analysed to use the Anova. There are difference of structure andcomposition of type of compiler of forest mangrove in Countryside Kopi and Minanga. Forestof Mangrove Countryside Kopi lapped over by 5 type mangrove which dominansi byBruguiera gymnorrhiza (117,11). Forest of Mangrove of Countryside Minanga lapped overby 7 type mangrove which dominansi by Rhizophora apiculata (91%). Structure Andcomposition of type of mangrove Countryside Kopi and Countryside Minanga have an effecton the reality to mosquito closeness. Mosquito closeness in forest of mangrove CountrysideKopi and Countryside Minanga is 38,7 and 21,7 tail/ mÂ².